Comparative Impacts of Scala Vestibuli Versus Scala Tympani Cochlear Implantation on Auditory Performances and Programming Parameters in Partially Ossified Cochleae. Issue 6 (July 2018) - Trudel, Mathieu; Côté, Mathieu; Philippon, Daniel; Simonyan, David; Villemure-Poliquin, Noémie; Bussières, Richard
Abstract : Objective: To compare scala vestibuli versus scala tympani cochlear implantation in terms of postoperative auditory performances and programming parameters in patients with severe scala tympani ossification. Study Design: Retrospective case-control study. Setting: Tertiary referral center. Patients: One hundred three pediatric and adult patients who underwent cochlear implant surgery between 2000 and 2016. Three groups were formed: a scala vestibuli group, a scala tympani with ossification group, and a scala tympani without ossification group. Patients were matched based on their age, sex, duration of deafness, and side of implantation (ratio of 1:2:2). Interventions: Postoperative evaluation of auditory performances and programming parameters following intensive functional rehabilitation program completion. Main Outcome Measures: Multimedia adaptive test (MAT), hearing in noise test (HINT SNR +10 dB, HINT SNR +5 dB, and HINT SNR +0 dB), impedances, neural response telemetry thresholds (NRT), neural response imaging thresholds (NRI), comfortable levels (C-levels), and threshold levels (T-levels) were compared between groups. Results: Twenty-one patients underwent scala vestibuli cochlear implantation: 19 adults and two children. Auditory performances were similar between groups, although sentence recognition in a noisy environment was slightly higher in the scala vestibuli group. Impedance values were also higher in the scala vestibuli group, but all other programming parameters were similar between groups. Conclusions: We present the largest series of patients with scala vestibuli cochlear implantation. This approach provides at least comparable auditory performances without having any deleterious effects on programming parameters. This viable and useful insertion route might be the primary surgical alternative when facing partial cochlear ossification.